Developing students motive achievement through Torrance concept in conjunction with gamification - Punyawee Duanyai; Prasart Nuangchalerm (CV. FOUNDAE, 2024)
Background: Motive achievement plays a crucial role in students academic success and personal development. To enhance this, the study integrates Torrance future problem-solving framework with gamification strategies.Aim: This classroom action research aims to improve the motive achievement of 11th-grade students by implementing structured, problem-solving-oriented learning activities that foster motivation and engagement.Method: The study involved 20 Grade 11 students and utilized lesson plans incorporating Torrance’s framework and gamification. Data was collected through motive achievement tests, observations, and interviews, and analyzed using means, percentages, and standard deviations over three cycles.Results: The findings demonstrated a steady increase in the percentage of students meeting the success criteria: 25 percent in cycle 1, 55 percent in cycle 2, and 75 percent in cycle 3. This indicates a significant improvement in motive achievement through the integration of Torrance concept and gamification.Conclusion: The study concludes that this innovative approach effectively enhances motive achievement and can be a valuable instructional strategy in science classrooms. Future research could explore its application in other subjects or educational levels to validate and extend its impact.